Toxicity Studies and Phytochemical Screening of Ficus Racemosa and Kalanchoe Pinnata: Pharmaceutical Science-Pharmacology - Teja Pavani, A.Naga; Sheela, Dr.D.; Ramesh, Dr.L.; Sirisha Goli, Dr. (International Journal of Life Science and Pharma Research, 2023)
Kalanchoe pinnata and Ficus racemosa are naturally occurring plant products that are gaining importance because of their excellent medicinal properties. Determining the toxicity of a plant extract is crucial, based on which the therapeutic dose of extracts can be adjusted. The present study evaluates phytochemical screening and toxicity studies (acute and sub-acute) of the Kalanchoe pinnata and Ficus racemosa plant products. Phytochemical screening showed the presence of alkaloids, tannins, flavonoids, steroids, phenols, and glycosides. The acute toxicity study of both the plant extracts was performed in Wistar albino rats at a single dose of 2000mg/kg body weight in both genders. Sub-acute toxicity study was performed in Wistar albino rats (both male and female) for 28 days at various doses of 500, 1000, and 2000 mg/kg body weight. The evaluation results of the acute toxicity study did not show any signs of toxicity, behavioral changes, mortality, or differences in gross histopathology appearance. The results of the sub-acute toxicity study also showed no changes in body weight, toxic signs, mortality, or behavioral changes. All biochemical and hematological parameters were in normal ranges comparable to the control group’s. At the end of the treatment period, all the rats were sacrificed, and the liver and kidneys were sent for histopathological examination. No abnormalities were observed in the treatment groups. The present study concludes that both plant extracts are safe, and the LD50 of both plant extracts was above 2000mg/kg bw.